V=x(16-3x)(16-3x)

Simple and best practice solution for V=x(16-3x)(16-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for V=x(16-3x)(16-3x) equation:



=V(16-3V)(16-3V)
We move all terms to the left:
-(V(16-3V)(16-3V))=0
We add all the numbers together, and all the variables
-(V(-3V+16)(-3V+16))=0
We multiply parentheses ..
-(V(+9V^2-48V-48V+256))=0
We calculate terms in parentheses: -(V(+9V^2-48V-48V+256)), so:
V(+9V^2-48V-48V+256)
We multiply parentheses
9V^3-48V^2-48V^2+256V
We do not support eVpression: V^3

See similar equations:

| .7c-7=4c+17 | | 4(x-2)^2=12 | | 3x²+13x-10=0 | | 3(5-2h)-9=-30 | | V=x(20-5x)(20-5x) | | 8y-10-4y+9=0 | | x+4=5x+86 | | 5x-20=15x | | 78.75+80.25x=40+95.75 | | x+1+2x-10=12 | | 8y-10-4y=9+0 | | 5(w-2)=9w+2 | | 8(x+5)-5=35 | | V=x(10-3x)(10-3x) | | 4n+2=4(1/3n-2/3) | | 3/11w+5=5 | | 15x-4=40+1 | | -3x2+243=0 | | (58x(-0.4x^2))-(3x+12)=0 | | x-2+6=2x-13 | | 12n+12=10n | | 5*n+2=3*n-6 | | (58x(-0.4x^2))-(3x+12)=x | | 2.5+10m=7.42 | | x=(58x(-0.4x^2))-(3x+12) | | 12n+12=10 | | (4x+1)^2=4 | | 2/5(4x-1)-2/5=3/5(4x-2)-4/5x | | 5x+19=4x+10 | | -177=-2-7(1-8m) | | -7n+6(-6n+5)=331 | | -5x2+245=0 |

Equations solver categories